STUDI DESKRIPTIF FAKTOR-FAKTOR YANG MEMPENGARUHI PRILAKU CARING PERAWAT DI RUMAH SAKIT BALADHIKA HUSADA JEMBER - Akhmad Efrizal amrullah; Emi Elliya Astutik; Achmad Djalil Ahbab (Jurnal Kesehatan dr. Soebandi, 2021)
Introduction: Caring behavior is very important for nurses to have because it illustrates the quality of nursing care, especially for nurses who work in inpatient units. There are three factors that can influence the level of caring behavior, namely individual, psychological and organizational factors. Meanwhile, caring behavior is assessed from Knowing, Being With, Doing For, Enabling, and Maintaining Belief. Objective: To describe the factors that influence the caring behavior of nurses in Baladhika Husada Jember Hospital. Methods: Nonexperimental design with descriptive type, in which the approach was cross sectional, carried out for 1 month and involved 62 respondents. Results: 47 respondents stated that the three factors above had an influence on caring behavior and 15 respondents stated that it had no effect, while the caring behavior of respondents in the good category was 58 people and 4 people were not good. Analysis of data using the One-Sample Binominal test at alpha (α) = 0.05, has the p-value = 0.000, which illustrates the difference between the factors that influence caring behavior towards nurses caring behavior. Conclusion: The factors that influence caring behavior are directly proportional to caring behavior, meaning the better factors that influence caring behavior, the better nurses caring behavior level. Maintaining and improving caring behavior requires good effort and cooperation between the hospital manager which is the place for health services and nurses as nursing care providers.